2018
DOI: 10.1002/med.21489
|View full text |Cite
|
Sign up to set email alerts
|

Heparin mimetics with anticoagulant activity

Abstract: Heparin, a sulfated polysaccharide belonging to the glycosaminoglycan family, has been widely used as an anticoagulant drug for decades and remains the most commonly used parenteral anticoagulant in adults and children. However, heparin has important clinical limitations and is derived from animal sources which pose significant safety and supply problems. The ever growing shortage of the raw material for heparin manufacturing may become a very significant issue in the future. These global limitations have prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 229 publications
(451 reference statements)
1
36
0
1
Order By: Relevance
“…There was a clear trend of increasing potency with increasing molecular weight, as seen in previous studies. [10,25] The data are thus presented in Figure 3A,C for 1:1 copolymers of MW 20 kDa, and in Figures S13-S18 and Tables S15-S17, Supporting Information for 1:1 copolymers of different MW and those with different monomer ratios. Unfractionated heparin (UFH) was used as the standard over the range of 1.0 -150.0 µg mL −1 , equivalent to 0.1-15.0 IU mL −1 .…”
Section: Activated Partial Thromboplastin Time and Thrombin Clotting mentioning
confidence: 99%
See 2 more Smart Citations
“…There was a clear trend of increasing potency with increasing molecular weight, as seen in previous studies. [10,25] The data are thus presented in Figure 3A,C for 1:1 copolymers of MW 20 kDa, and in Figures S13-S18 and Tables S15-S17, Supporting Information for 1:1 copolymers of different MW and those with different monomer ratios. Unfractionated heparin (UFH) was used as the standard over the range of 1.0 -150.0 µg mL −1 , equivalent to 0.1-15.0 IU mL −1 .…”
Section: Activated Partial Thromboplastin Time and Thrombin Clotting mentioning
confidence: 99%
“…Increased anticoagulant activity was generally correlated with increased molecular weight, a general trend seen in previous studies of heparin mimetics. [10] However, it is clear that there were some intriguing structure-activity relationships beyond molecular weight. Variations in monomer composition (and distribution) resulted in copolymers with different affinities for their target proteins, as reflected in some interesting and subtle changes in anticoagulant activity.…”
Section: Activated Partial Thromboplastin Time and Thrombin Clotting mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it inhibits tumorigenic actions induced by IIa and FXa, conferring a survival benefit in cancer patients and the regression of primary tumors [9]. However, the use of heparin can cause side effects such as the development of thrombocytopenia, arterial embolism, bleeding complications, and even death of the patient [10]. In addition, the problem of heparin deliberate contamination with super sulfated chondroitin can induce death of the patient [11].…”
Section: Introductionmentioning
confidence: 99%
“…20 Biological heparin, a high molecular weight polysaccharide, has a long history of use as a clinical anticoagulant, which continues to this day. [21][22] Through over a decade of research, a pentasaccharide representing the minimum active heparin sequence was characterized, and later a synthetic version was commercialized as the low molecular weight anticoagulant, fondaparinux (See Figure 1b). 23 Importantly, it was shown that sulfated IdoA was required for binding to AT.…”
Section: Introductionmentioning
confidence: 99%